The experiences of men following recurrent miscarriage in an Irish tertiary hospital: A qualitative analysis - Tommy Harty; Maria Trench; Orla Keegan; Keelin O'Donoghue; Daniel Nuzum (Wiley, 2022)
Abstract Introduction Miscarriage is one of the most common complications of pregnancy, and recurrent miscarriage affects approximately 1% of couples. The psychological impact of early pregnancy loss on women has been well documented in the literature; however, the burden of miscarriage on men remains largely unexplored. Methods This qualitative research involved semi‐structured interviews with five men whose partners had experienced at least two consecutive miscarriages. Participants were recruited through an early pregnancy loss clinic in a large, tertiary maternity hospital. Interviews were recorded and transcribed verbatim and analysed thematically. Results Recurrent miscarriage had a pronounced psychological impact on all the men interviewed, which worsened with each successive miscarriage. Three primary themes were developed from the data: (1) the deeply emotional experiences of men following recurrent miscarriage; (2) frustrations experienced during the provision of support following recurrent miscarriage; and (3) a sense of feeling unimportant. Lack of timely provision of information about miscarriage as well as lack of access to services were highlighted as deficiencies in the quality of care provided after recurrent miscarriage. Conclusion The experiences of men after recurrent miscarriage are based largely on their assumed role as the protector and supporter of their partner, which often results in neglect of their own psychological needs. The support required by men is similar to that required by women, and greater access to information and services is needed to improve the experiences of men following recurrent miscarriage. Patient Contribution Participants were recruited through the Pregnancy Loss Clinic at Cork University Maternity Hospital and were identified by specialist midwives. Participants were approached and interviewed by one of the researchers. Participation was voluntary and the men received no financial contribution for their time.